Modelamiento futuro y cambio climático: Proyección de los ecosistemas naturales de la provincia de El Oro bajo un escenario de cambio climático IPCC – AR5 – RCP 6.0. - Poma Sarango, Marco Antonio (2023)
Due to fossil fuel consumption and deforestation, anthropogenic activity has aggravated climate change, a natural phenomenon. This has resulted in phenomena such as climate variation. Throughout the world and in our study area (El Oro), anthropogenic pressures associated with land use change are affecting natural ecosystems, resulting in increased vulnerability to climate change and changes to distribution ranges. Natural ecosystems are increasingly vulnerable to climate change and may even change distribution ranges as a result of anthropogenic pressures associated with land use change. We evaluated the potential distribution of ecosystems in the province of El Oro by the year 2080 (2061 -2080), using as a climate change scenario one of the Representative Concentration Pathways (RCP), proposed by the IPCC in the Fifth Assessment Report (AR5) - RCP 6.0, with the development of Biomod2 species distribution models (SDM).The results showed that the ecosystems of the province of El Oro are vulnerable to climate change, as the majority of the 19 ecosystems analyzed (15) could present a contraction of their distribution ranges, varying both in latitude and longitude, in search of areas that are climatically and topographically suitable for recovering its ecological functionality. The most vulnerable ecosystem is the Catamayo-Alamor low montane seasonal evergreen forest (BeBn01), which could disappear under the influence of climate change, due to the lack of suitability in the biophysical conditions analyzed within the provincial territory; in contrast, the ecosystems Southern Valleys desert shrubland (AdBn01) and Jama-Zapotillo lowland deciduous forest (BdTc01), would expand their distribution ranges. Keywords: climate change, ecosystems, species distribution models, biomod2, El Oro.